Adherence to four healthy lifestyle factors and their influencing factors among residents aged 35 – 75 in South China: a cross-sectional survey - Wenyan HE; Xingyi ZHANG; Chunqi WANG; Xueke BAI; Yang YANG; Wei XU; Lijuan SONG; Yan ZHANG; Hao YANG; Xi LI; Jianlan CUI (Zhongguo gonggong weisheng)
ObjectiveTo investigate the adherence to four healthy lifestyle factors among residents aged 35 – 75 years in South China and to identify the influencing factors, providing a reference for promoting healthy lifestyles in this region. MethodsA cross-sectional survey was conducted from September 2015 to November 2022 using a typical sampling method in South China. A total of 289 937 residents aged 35 – 75 years from Guangdong province, Guangxi Zhuang Autonomous Region, and Hainan province were included. The adherence to four healthy lifestyle factors, namely non-smoking, no or moderate alcohol consumption, adequate physical activity, and a healthy diet, was analyzed. Multivariable unconditional logistic regression models were used to identify the influencing factors. ResultsAmong the 80,385 residents aged 35 – 75 years included in the final analysis, the number of participants adhering to non-smoking, no or moderate alcohol consumption, adequate physical activity, a healthy diet, and all four healthy lifestyle factors were 66 765, 78 576, 23 807, 18 391, and 6 707, respectively. The corresponding adherence rates were 83.1%, 97.7%, 29.6%, 22.9%, and 8.3%, and the standardized adherence rates were 77.95%, 97.26%, 27.66%, 23.42%, and 7.31%, respectively. Multivariable unconditional logistic regression analysis showed that female residents, those aged 70 – 75 years, those with a college degree or higher, those who were married, and those with a history of myocardial infarction/coronary revascularization/stroke were more likely to adhere to non-smoking. Residents aged 40 – 59 years, those with a junior high school education, farmers, rural residents, those with an annual household income of 10 000 – 50 000 yuan, and those with a history of hypertension/diabetes were less likely to adhere to non-smoking. Female residents, those aged 70 – 75 years, and those who were married were more likely to adhere to no or moderate alcohol consumption. Residents aged 50 – 59 years, farmers, and rural residents were less likely to adhere to no or moderate alcohol consumption. Female residents, those aged 50 – 75 years, those with a high school education or higher, those with an annual household income of > 50 000 yuan, and those with a history of hypertension/diabetes or myocardial infarction/coronary revascularization/stroke were more likely to adhere to adequate physical activity. Residents aged 40 – 49 years, those with a junior high school education, farmers, rural residents, and those with an annual household income of 10 000 – 50 000 yuan were less likely to adhere to adequate physical activity. Female residents, those aged 50 – 75 years, those with a high school education or higher, and those with an annual household income of > 50 000 yuan were more likely to adhere to a healthy diet. Residents with a junior high school education, farmers, rural residents, and those with social medical insurance were less likely to adhere to a healthy diet. Female residents, those aged 50 – 75 years, those with a high school education or higher, those with an annual household income of > 50 000 yuan, and those with a history of myocardial infarction/coronary revascularization/stroke were more likely to adhere to all four healthy lifestyle factors. Residents aged 40 – 49 years, those with a junior high school education, farmers, rural residents, and those with an annual household income of 10 000 – 50 000 yuan were less likely to adhere to all four healthy lifestyle factors. ConclusionsThe adherence rates to non-smoking, no or moderate alcohol consumption, adequate physical activity, and a healthy diet were low among residents aged 35 – 75 years in South China. Gender, occupation, residence, and history of myocardial infarction/coronary revascularization/stroke were common influencing factors for adherence to the four healthy lifestyle factors.